1991
DOI: 10.1111/j.1939-1676.1991.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Concentrations Measured by a Chromogenic Assay in Portal and Peripheral Venous Blood in Ten Dogs With Portosystemic Shunts

Abstract: A chromogenic Limulus amebocyte lysate assay was used to measure portal and peripheral venous endotoxin concentrations in ten medically managed dogs undergoing surgery for correction of a single extrahepatic portosystemic shunt. In all dogs, both peripheral and portal venous blood samples were obtained at the time of surgical manipulation of the anomalous vessel. In six dogs, peripheral venous samples were obtained an average of 8.0 months after surgery. Five physically normal dogs without biochemical or histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results suggest that the majority of adult healthy dogs harbour a bacterial population in the liver parenchyma, but a common pattern cannot be defined. It is known that under normal physiological conditions, the microbial population present in the liver is kept at levels compatible with a healthy status (ie, without resulting in infection) by the liver mononuclear phagocytic system, mainly represented by the Kupffer cells (Peterson andothers 1991, Center 1996). Conversely, in the presence of vascular compromise resulting in liver hypoxia, the existence of a bacterial population in the liver may elicit severe clinical symptoms (Bunch 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the majority of adult healthy dogs harbour a bacterial population in the liver parenchyma, but a common pattern cannot be defined. It is known that under normal physiological conditions, the microbial population present in the liver is kept at levels compatible with a healthy status (ie, without resulting in infection) by the liver mononuclear phagocytic system, mainly represented by the Kupffer cells (Peterson andothers 1991, Center 1996). Conversely, in the presence of vascular compromise resulting in liver hypoxia, the existence of a bacterial population in the liver may elicit severe clinical symptoms (Bunch 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative 85 bacteria are present in the small intestine and therefore LPS is absorbed from the gut 86 and into the portal vein (Peterson et al, 1991;Howe et al, 1997). LPS has been 87 shown to play a positive role in liver regeneration in rodent models (Cornell, 1985a, 88 b, 1990; Gao et al, 1999).…”
Section: Lipopolysaccharide (Lps) or Endotoxin Is A Component Of The mentioning
confidence: 99%
“…For decades, there has been great interest in unraveling the pathophysiology of bacterial translocation in cirrhosis [3]. Experimental data derived from animal studies demonstrated portal and systemic bacteremia, predominantly Gram-negative organisms, in cirrhotic animals with portal hypertension [4-6]. Research conducted 20-30 years ago suggested an important role for endotoxemia in liver cirrhosis, but the assays available at that time were less sensitive and human portal blood sampling is challenging [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data derived from animal studies demonstrated portal and systemic bacteremia, predominantly Gram-negative organisms, in cirrhotic animals with portal hypertension [4-6]. Research conducted 20-30 years ago suggested an important role for endotoxemia in liver cirrhosis, but the assays available at that time were less sensitive and human portal blood sampling is challenging [6,7]. Recent detection of bacterial translocation during HIV infection, thought to result from increased gut permeability, provided a plausible cause of systemic immune activation; however, parallel studies in, HBV, HCV and HIV-HCV co-infection demonstrated that bacterial translocation is strongly associated with cirrhosis, raising questions of cause and effect [8-11].…”
Section: Introductionmentioning
confidence: 99%